Fabrication and characterization of spin-assisted and dip-coated PEDOT PSS and poly(diallydimethylammonium chloride) nanofilms for organic light-emitting diode - Quesada, Maria Gabriela B.; Binag, Christina A. (2011)
Organic lighi emitting diodes (OLED) have extended its domain of application in the area of flat panel displays due to their potential properties, brightness efficiency, extended lifetime and low production cost. The study aims to prepare and characterize nanofilms of Poly (3,4 ethylenedioxvthiophene):Poly (styrenesulfonate) (PEDOT:PSS) and Poly(diallyldimethylammonium chloride) (PDADMAC) for the fabrication of an OLED. PEDOT:PSS was chemically polymerized using (NH4)2S2O2 oxidant and FeCl, catalyst. Absorbances of different solutions of synthesized PEDOT:PSS were determined using a UV-visible spectrophotometer. The glass slides and ITO-coated slides (10x20 mm) substrates were degreased and functionalized. In dip-coating, the treated substrate was then initially immersed in 0.01M PDADMAC solution for 15 min, followed by immersion in 3% (w/v) PEDOT:PSS solution. In spin-coating, PDADMAC and PEDOT:PSS were deposited alternately on the substrate with spin speed of 2500 rpm for 30 sec. The cycles for two techniques were repeated until 10 bilayers were achieved. Each bilaver exhibited absorbance peaks at 370, 560 and 850 nm due the dark blue PEDOT. The SEM micrographs of PEDOT:PSS surfaces revealed globular structures. Atomic force micrographs showed average roughness of 1.000 nm and 14.697 nm, for spin-assisted and dip-coated films, respectively. An OLED was fabricated using PEDOT:PSS/PDADMAC films as the hole transport layer. The current-voltage graph of prepared OLED showed a diode characteristic.
Keywords: Light emitting diodes